2019
DOI: 10.1111/1748-8583.12230
|View full text |Cite
|
Sign up to set email alerts
|

It is not just about paying your dues: Impact of generational cohort on active and passive union participation

Abstract: The lack of a validated measure of active–passive union participation and a dearth of research into the relationship between generational cohort and union participation challenge union leaders to develop policies and practices to facilitate union renewal. We address these issues by (a) developing a multidimensional measure of union participation that captures both active and passive components, (b) using structural equation modelling to validate the measure within a nomological framework, and (c) investigating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 59 publications
3
11
0
Order By: Relevance
“…First, our findings are consistent with Bennett et al's (2008) idea of digital natives as the younger the union member, the more open they are (and the more open they want the union to be) to the use of online modes of communication such as email, text and instant messaging email (Campbell et al, 2017;Ignatius & Hechanova, 2014). Second, the establishment of differences in union-member communication preferences and perceptions supports authors such as Lyons et al (2015), and Smith, Halinski, and Duxbury (2019) who have defended the idea of generational cohort as a useful lens through which to explore potential differences in attitudes, values and perceptions. Our findings also offer strong support to Mannheim's theory of generations and encourage unions, researchers and organisations to take generational cohort into account when designing how best to encourage and support union renewal.…”
Section: Impact Of Generational Cohortmentioning
confidence: 86%
See 2 more Smart Citations
“…First, our findings are consistent with Bennett et al's (2008) idea of digital natives as the younger the union member, the more open they are (and the more open they want the union to be) to the use of online modes of communication such as email, text and instant messaging email (Campbell et al, 2017;Ignatius & Hechanova, 2014). Second, the establishment of differences in union-member communication preferences and perceptions supports authors such as Lyons et al (2015), and Smith, Halinski, and Duxbury (2019) who have defended the idea of generational cohort as a useful lens through which to explore potential differences in attitudes, values and perceptions. Our findings also offer strong support to Mannheim's theory of generations and encourage unions, researchers and organisations to take generational cohort into account when designing how best to encourage and support union renewal.…”
Section: Impact Of Generational Cohortmentioning
confidence: 86%
“…The few studies that explore issues associated with union renewal through a generational cohort lens (Cates, 2014;Dufour-Poirier & Laroche, 2015;Hodder, 2014;Smith, Halinski, & Duxbury, 2019) do, however, provide empirical support to the idea that generational cohort has relevance to this discussion. Cates (2014), for example, found that although millennials demonstrated the most pro-union attitudes of any cohort in popular polling, when given the choice, boomers (36%) were least likely and millennials most likely (55%) to opt out of their union [Gen Xers (41%) were in-between].…”
Section: Generational Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…This research adds to the growing (but limited) body of empirical research linking generations and unions (Cates, 2014;Smith, Halinski and Duxbury, 2019) and communication between unions and their members (Rivers and Truitt, 2014). It also provides practical information to union leaders on how to target their communications to different generations of members.…”
Section: It's Not Just What You Say But How You Say It: a Case Studymentioning
confidence: 89%
“…Also problematic is the fact that most studies of union participation take an etic perspective (e.g. Smith, Duxbury and Halinski, 2019) such that the view of the researcher takes preeminence when the construct is conceptualized. In fact, our review of the extant literature in the area uncovered no examples of academic studies on union participation employing an emic perspective (i.e., research that takes the standpoint of the social group being studied).…”
Section: Union Participation Through An Emic Lens: Comparing Emic Andmentioning
confidence: 99%